Stray voltage problems in dairy farms and effects on animal behavior - Gonulol, E.; Polat, Refik; Ulger, P.; Kayisoglu, B.; Kuscu, H.; Toruk, F.; Polat, C. (2008)
Stray voltage is a small voltage measured between two points that can simultaneously be contacted bya cow. A current will flow between these points. The amount of current depends on the voltage and theresistance of the animal. Reactions of animals to mild electric shocks caused by stray voltage havebeen reported to include behavioral changes, changes in milking characteristics of dairy cows andchanges in production performance. This study evaluated the presence or absence of stray voltage ondairy farms. Questionnaires related to the history of the situation and animal reactions were also usedin the study. Experiments were carried out on 51 dairy farms in Turkey. All farms had more than 30milking cows which are milked by using pipe line milking systems. Stray voltage problems were foundon 12 farms (23%). The relationship between the presence of stray voltage and behavioral change onthe dairy farms was statistically significant (P=0,002). Based on the results, stray voltage sources onthe farms were mostly attributed to faulty wiring, faulty equipment and improper grounding.
Keywords: Animal behavior; Dairy farms